Optimization of Curve Correction in the Plan Using Computer Modeling to Improve Train Safety - Khmelevska, N. P.; Kurhan, M. B.; Kurhan, D. M. (Science and Transport Progress, 2024)
Purpose. The authors intend to develop and implement innovative approaches to optimizing curve correction in the plan of railway tracks using computer modeling. This process aims to: improve traffic safety; improve the smoothness of the ride, which increases passenger comfort; eliminate speed limits on curved sections, which reduces travel time and increases railroad capacity; reduce track maintenance and rolling stock repair costs. The use of special software to simulate various scenarios of train traffic along the adjusted curves will allow us to assess the impact of the train flow structure on the speed, rolling stock dynamics, and track condition. Methodology. The study is based on the theory of mathematical modeling and numerical calculation methods. To find the best option for the reconstruction of railway sections, the line is considered as a complex system consisting of various infrastructure facilities. Due to their unsatisfactory technical condition, these facilities may limit the speed of traffic on certain sections. The solution to this problem is complicated due to the interdependence of such objects: the reduction of travel time on a particular section is not linear, and obtaining accurate results requires traction calculations taking into account various options for eliminating speed limits. Findings. A calculation algorithm for optimizing long sections of the railway plan is proposed. The algorithm allows to take into account the desired direction of shifts in the curves, which greatly facilitates the optimization process. An example of calculations based on the proposed algorithm is given, which demonstrates the effectiveness of the approach. Originality. The scientific and applied problem of optimizing the process of adjusting railway curves in the plan has been solved. This helps to improve the safety and speed of trains through the introduction of the latest computer modeling methods. Practical value. The implementation of the proposed technology for optimizing the railway plan will significantly increase the speed and safety of train traffic, as well as increase the throughput capacity of railway lines. This will be an important step for the integration of Ukrainian railways into the European transportation system.